Partners and relatives. Articulating modernity and tradition in Portuguese large family firms - Lima, A. P. de. (International Journal of Business and Social Science, 2013)
Large family enterprises are different from other kinds of large firms in Portugal. The formation of kinship relationships found in the social context of large family firms is also of a different nature than those found in other social groups. Both features are due to the overlapping of family and economic relations that characterises large family firms. Based on research developed among large Portuguese family firms, this article analyses changes in the succession for leadership positions in these organisations over the last 100 years. Although these wealth entrepreneurial families are strongly rooted on traditional social values (as they claim their aristocratic origin) they develop strong strategies to integrate modernity symbols and meritocratic criteria in the incorporation of relatives into the firm. I will argue that the articulation of family tradition with modern economic rationality is central to the survival of traditional large family firms in contemporary world economy.